2020
DOI: 10.1140/epjc/s10052-020-08560-0
|View full text |Cite
|
Sign up to set email alerts
|

Lense–Thirring precession and gravito–gyromagnetic ratio

Abstract: The geodesics of bound spherical orbits i.e. of orbits performing Lense–Thirring precession, are obtained in the case of the $$\varLambda $$ Λ term within the gravito-electromagnetic formalism. It is shown that the presence of the $$\varLambda $$ Λ -term in the equations of gravity leads to both relativistic and non-relativistic corrections in the equations of motion. The contribution of the $$\varLambda $$ Λ -term in the Lense–Thirring precession is interpreted as an additional relativistic correction and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Finally, since the well-known Lense-Thirring (LT) precession can be obtained from Eq. (20) in the slow rotation limit, our above statement about the effect of Λ on the frame dragging effect can be regarded as the continuation of investigation of LT precession in the presence of Λ [25]. It was shown that then an additional term appears which contains Λ…”
Section: Schwarzschild-de Sitter Vs Kerr-de Sitter Bhsmentioning
confidence: 68%
“…Finally, since the well-known Lense-Thirring (LT) precession can be obtained from Eq. (20) in the slow rotation limit, our above statement about the effect of Λ on the frame dragging effect can be regarded as the continuation of investigation of LT precession in the presence of Λ [25]. It was shown that then an additional term appears which contains Λ…”
Section: Schwarzschild-de Sitter Vs Kerr-de Sitter Bhsmentioning
confidence: 68%
“…Therefore, we can falsify or constrain the parameter space of extended/modified theories of gravity by comparing their post-Newtonian (PN) and parameterized post-Newtonian (PPN) predictions to the corresponding GINGER measurements. The general purpose is to demonstrate that theories of gravity can be constrained not only by astrophysical and cosmological observations or space satellites but also by terrestrial experiments that can be, in principle, more easily tuned and controlled [79,80].…”
Section: Introductionmentioning
confidence: 99%
“…where S visc is the viscous force per unit mass, ρ is the density, P is the pressure, and v × h is the gravitomagnetic force according to gravito-electromagnetic (GEM) formalism [20,24]. In order to consider the relativistic effects, the GR potential in Eq.…”
Section: Nodal and Apsidal Frequenciesmentioning
confidence: 99%
“…For the current the numerical value Λ = 1.11 × 10 −52 m −2 [13], it is predicted that with an increase in accuracy and statistics in observational data, the observations of gravitational lensing, groups and clusters of galaxies, the flow of galaxies in the vicinity of the local group, properties of cosmic voids [14] can provide informative tests to detect the effects associated with the cosmological constant [15]. The influence of Λ on various effects and the possibility to obtain constraints associated with Λ-term is considered in [16][17][18][19][20]. Particularly, it was shown that the Λ-term is able to provide a solution for the Hubble tension problem [21].…”
Section: Introductionmentioning
confidence: 99%